IGSF11 is required for pericentric heterochromatin dissociation during meiotic diplotene. - Bo Chen; Gengzhen Zhu; An Yan; Jing He; Yang Liu; Lin Li; Xuerui Yang; Chen Dong; Kehkooi Kee (PLoS Genetics, 2021)
Meiosis initiation and progression are regulated by both germ cells and gonadal somatic cells. However, little is known about what genes or proteins connecting somatic and germ cells are required for this regulation. Our results show that deficiency for adhesion molecule IGSF11, which is expressed in both Sertoli cells and germ cells, leads to male infertility in mice. Combining a new meiotic fluorescent reporter system with testicular cell transplantation, we demonstrated that IGSF11 is required in both somatic cells and spermatogenic cells for primary spermatocyte development. In the absence of IGSF11, spermatocytes proceed through pachytene, but the pericentric heterochromatin of nonhomologous chromosomes remains inappropriately clustered from late pachytene onward, resulting in undissolved interchromosomal interactions. Hi-C analysis reveals elevated levels of interchromosomal interactions occurring mostly at the chromosome ends. Collectively, our data elucidates that IGSF11 in somatic cells and germ cells is required for pericentric heterochromatin dissociation during diplotene in mouse primary spermatocytes.